Unexpected retinal fluid compartment responses with anti-VEGF therapy in polypoidal choroidal vasculopathy: a case report of four patients - Gilead, Noa; Chong, Yu Jeat; Ibrahim, Farah N. I.; Sun, Christopher; Teo, Kelvin Y. C.; Cheung, Chui Ming Gemmy (Frontiers in Ophthalmology, 2024)
This case series describes responses to faricimab treatment in opposite directions in different fluid compartments in four patients with polypoidal choroidal vasculopathy (PCV). Despite reductions in retinal fluid (SRF) and stable visual acuity following treatment, all patients developed retinal pigment epithelium (RPE) elevation. Over a 12–15 months follow-up, three patients exhibited a gradual decrease in RPE elevation, with one case resolving completely. These findings suggest that fluid compartments in PCV may respond differently to treatment and add to the understanding of PCV by highlighting the complex interplay between different retinal fluid compartments in response to treatment.